The impact of the COVID-19 pandemic on critically ill patients with acute stroke and diabetic ketoacidosis - Kılıç, Mazlum; Tekyol, Davut (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. This study aimed to compare the hospitalization rate, mortality rate and morbidity status of patients hospitalized with stroke and diabetic ketoacidosis (DKA) before and during the COVID-19 pandemic. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The data of 2522 patients who applied to the emergency department (ED) before and during the pandemic were evaluated. A Poisson regression analysis was used to examine the number of presentations between two different periods. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Stroke cases during the pandemic era were compared to those during the pre-pandemic period, and it was shown that the mortality rate for stroke patients during the pandemic period was much higher. Treatment-related ED presentations decreased significantly during the pandemic period, particularly among patients aged 75–84 years. Rates of ED presentation decreased by 84 percent (IRR: 0.14, 95 percent CI: 0.03-0.59) in those with DKA and by 37 percent (IRR: 0.67, 95 percent CI: 0.53- 0.75) in those with stroke during the pandemic period. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Conclusion: Stroke and DKA admissions decreased during the pandemic, but the rate of stroke mortality increased statistically 3.375 times. Getting emergency medical care increases their chances of survival. Even in a COVID-19 outbreak, treatment is critical.